Research on Engine Speed Control System Based on Fuzzy Adaptive PID Controller - Wang, Hairui; Wang, Lu; Liao, Yongyi; Yang, Hongwei (Manufacturing Technology Journal, 2019)
Traditional PID fails to meet the requirements in control precision and response speed while implementing a nonlinear control. Such problem can be easily solved by adaptive fuzzy PID, which indicates that the adaptive fuzzy PID will realize the precise control in engine speed control system, a typical nonlinear system. This paper first discusses the mathematical control model of diesel engine speed-control system and the characteristics of the traditional PID control. Then, the speed control principle of the adaptive fuzzy PID controller is analyzed. Besides, the membership function of fuzzy logical, the fuzzy logical variable and the fuzzy reasoning rules are determined. Next, the adaptive correction method is briefly introduced. Finally, the model of traditional PID and adaptive fuzzy PID controller are simulated and the same disturb is added into the control systems. The simulation results show that the adaptive fuzzy PID controller has better performance in dynamic response and robustness than that of traditional PID.
Keywords: Diesel Engine; Adaptive fuzzy PID controller; Speed-control system